Multisystem Health Consequences of Prenatal Hyperandrogenism in Offspring - Dong Liu; Wenxi Chen; Qian Zhong (Clinical and Experimental Obstetrics & Gynecology)
Objective: Prenatal hyperandrogenism, characterized by elevated androgen levels during pregnancy, has significant multisystem impacts on offspring health. This review systematically examines the effects of prenatal hyperandrogenism on the cardiovascular, metabolic, reproductive, and behavioral health of offspring. By analyzing existing research, this review aims to provide a comprehensive understanding of the long-term health impacts of prenatal hyperandrogenism, offering insights for clinical management and prevention of related diseases. Mechanism: A comprehensive search was performed in PubMed database with the key words: “hyperandrogenemia and child”, “hyperandrogenemia and offspring”, “androgen excess and child”, “androgen excess and offspring”, “prenatal hyperandrogenism”, “prenatal androgen excess”, and a combination of these terms to find quality articles published from 1995 to 2024. Findings in Brief: Elevated prenatal androgen levels disrupt normal fetal development, leading to long-term consequences such as cardiovascular dysfunction, including hypertension and cardiac hypertrophy, and metabolic abnormalities such as insulin resistance and metabolic syndrome. It has a significant impact on the long-term health of the offspring’s reproductive system, with potential links to conditions such as polycystic ovary syndrome (PCOS). Furthermore, prenatal hyperandrogenism is associated with increased risks of neuropsychiatric disorders, including autism spectrum disorder (ASD) and anxiety. Conclusions: Elevated prenatal androgen levels disrupt normal fetal development, leading to long-term cardiovascular, metabolic, reproductive, and neuropsychiatric disorders. The underlying mechanisms involve hormonal regulation, placental function, oxidative stress, gene expression alterations, and metabolic programming. Further research is needed to develop effective interventions to mitigate these adverse effects.